Wychowawcza funkcja Kościoła w dobie ponowoczesności - Filipczuk, Marek (Collectanea Theologica, 2018)
The educational function of the community is fulfilled through teaching, liturgy and pastoral undertakings. These are the fundamental functions of the Church. If the Good News which the Church proclaims is to remain the Light “which enlightens every man coming into the world”, the Church must remain the guarantor of conscience, its guardian, and the defender of the person, thus of humanity itself. The ecclesial character of Christian morality does not take away from conscience per se. It simply points to a need for its ecclesial interpretation since, apart from God, there is no other immutable basis for the absolute character of law and moral obligation. The parish plays an important role in the integral education of humans and the development of their faith. It is the most significant place in which the Christian community is formed. The parish, therefore, becomes a point of reference for persons seeking a living Church, looking for a place of authentic prayer and dialogue, a friendly community which attracts by means of an authentic Christian lifestyle. It is the community of faith that makes catechesis alive in its teaching, celebration (liturgy), as well as practice (diaconate). Thanks to these activities, meeting the Church in the parish becomes real and immediate – it is here that the daily life of the faithful encounters the reality of Salvation.